Bacteria Belonging to Pseudomonas typographi sp. nov. from the Bark Beetle Ips typographus Have Genomic Potential to Aid in the Host Ecology - Peral-Aranega, Ezequiel; Saati-Santamaría, Zaki; Kolařik, Miroslav; Rivas, Raúl; García-Fraile, Paula (Insects, 2020)
European Bark Beetle Ips typographus is a secondary pest that affects dead and weakened spruce trees (Picea genus). Under certain environmental conditions, it has massive outbreaks, resulting in the attacks of healthy trees, becoming a forest pest. It has been proposed that the bark beetle's microbiome plays a key role in the insect's ecology, providing nutrients, inhibiting pathogens, and degrading tree defense compounds, among other probable traits yet to be discovered. During a study of bacterial associates from I. typographus, we isolated three strains identified as Pseudomonas from different beetle life stages. A polyphasic taxonomical approach showed that they belong to a new species for which the name Pseudomonas typographi sp nov. is proposed. Genome sequences show their potential to hydrolyze wood compounds and synthesize several vitamins; screening for enzymes production was verified using PNP substrates. Assays in Petri dishes confirmed cellulose and xylan hydrolysis. Moreover, the genomes harbor genes encoding chitinases and gene clusters involved in the synthesis of secondary metabolites with antimicrobial potential. In vitro tests confirmed the capability of the three P. typographi strains to inhibit several Ips beetles' pathogenic fungi. Altogether, these results suggest that P. typographi aids I. typographi nutrition and resistance to fungal pathogens.
Keywords: beneficial; bacteriome; Ips typographus; Pseudomonas; bark beetle